Conductive properties and mechanisms of different polymers doped by carbon nanotube/polypyrrole 1D hybrid nanotubes. Issue 75 (19th August 2015) - Tan, Hong-xin; Xu, Xue-cheng
<x xml:space="preserve">Abstract</x> Polymers doped by MPPy hybrid nanotubes with enhanced conductivity and a reduced amount of carbon nanotubes.